2019
DOI: 10.3390/biom9060232
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis, Signaling, and Neurological Functions of Bile Acids

Abstract: Bile acids (BA) are amphipathic steroid acids synthesized from cholesterol in the liver. They act as detergents to expedite the digestion and absorption of dietary lipids and lipophilic vitamins. BA are also considered to be signaling molecules, being ligands of nuclear and cell-surface receptors, including farnesoid X receptor and Takeda G-protein receptor 5. Moreover, BA also activate ion channels, including the bile acid-sensitive ion channel and epithelial Na+ channel. BA regulate glucose and lipid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
126
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 194 publications
(222 reference statements)
2
126
0
6
Order By: Relevance
“…Bifidobacteria, which were more abundant in infants that did not receive antibiotics, are known to deconjugate bile acids to primary forms including cholic acid, which was positively correlated with bifidobacteria abundance 50,51 . Cholic acid can passively diffuse into the brain where it blocks signaling in the GABA a receptor 52 . Bifidobacteria may therefore be essential in regulating GABA signaling in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacteria, which were more abundant in infants that did not receive antibiotics, are known to deconjugate bile acids to primary forms including cholic acid, which was positively correlated with bifidobacteria abundance 50,51 . Cholic acid can passively diffuse into the brain where it blocks signaling in the GABA a receptor 52 . Bifidobacteria may therefore be essential in regulating GABA signaling in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, signaling pathways of bile acids may be initiated basically via two types of receptors, membrane as well as nuclear ones [6]. Given this, TUDCA/UDCA has now been recognized as a ligand of membrane receptors such as Takeda G-protein receptor 5 (TGR5) and sphingosine-1-phosphate receptor 2 (S1PR2) [7]. It has also been suggested that TUDCA/UDCA is transported into the cell via Na + /taurocholate co-transporter peptide (NTCP) and is then able to bind α5β1 integrin, transforming it into its active conformation by transferring β1 subunit [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that TUDCA/UDCA is transported into the cell via Na + /taurocholate co-transporter peptide (NTCP) and is then able to bind α5β1 integrin, transforming it into its active conformation by transferring β1 subunit [8][9][10]. Moreover, after internalization, TUDCA/UDCA can also activate nuclear receptors such as farnesoid X receptor (FXR) and glucocorticoid receptor (GR) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of feeding, metabolism, disease development, and homeostasis may be the result of their interactions and mutual influence [17]. On the one hand, bile acids not only facilitate transport of lipids and intestinal absorption but are also inflammatory agents and signaling molecules that effectively activate cell signaling pathways that regulate glucose, lipids, and energy metabolism [18]. On the other hand, accumulating studies have suggested that bile acids could activate certain receptors, such as the farnesoid X receptor (FXR) and the transmembrane G protein-coupled receptor 5 (TGR5), which improves glucose tolerance, insulin sensitivity, and energy metabolism [19].…”
Section: Introductionmentioning
confidence: 99%